Preparation and Characterization of Hydrogels Based on Homopolymeric Fractions of Sodium Alginate and Pnipaam - Encina-Rojas, M; Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Leal-Rifo, D (2013)
Graft copolymers were prepared by formation of an amide bond between poly-?-l-guluronic acid (MW 24,000), isolated from sodium alginate and the free amino group of PNIPAAm-NH2. SEM micrographs revealed the formation of a macroscopic network on the surface of the grafted hydrogels with a porosity diameter of 10-20 ?m. Semi-IPN hydrogels were prepared using different proportions of sodium poly-?-d-mannuronate (MW 21,000), isolated from sodium alginate and cross-linked PNIPAAm-NH2 polymers. SEM micrographs showed porosities of minor size (?5 ?m). Though both types of hydrogels are good water containers, the water retention capacity of graft copolymers is more than 50% higher than that of semi-IPN hydrogels. Both hydrogel types showed significant changes in swelling ratios between 20 and 45 °C: the swelling ratio decreases near the LCST of PNIPAAm. The water absorption and retention capacity of graft hydrogels increases with pH, reaching a maximum value at pH 7.0. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Sodium alginate; Homopolymeric fractions; PNIPAAm; Hydrogels; SEM